2009
DOI: 10.1556/mental.10.2009.3.5
|View full text |Cite
|
Sign up to set email alerts
|

A questionnaire based study of subjective sleep quality: The psychometric evaluation of the Hungarian version of the Groningen Sleep Quality Scale

Abstract: Jelen tanulmányban bemutatjuk a Groningen Alvásminôség Skála (Groningen Sleep Quality Scale) magyar verziójának 201 személy adatain nyugvó pszichometriai jellemzôit. A skálát két független mintán -123 egyetemista és 78 pszichiátriai beteg által kitöltött kérdô-ív alapján -vizsgáltuk meg. A Groningen Alvásminôség Skála belsô reliabilitása mindkét minta esetében kifejezetten jónak bizonyult, a Cronbach alfa értéke mindkét esetben meghaladta a 0,85-ös értéket. A skála validitás vizsgálatát 4 különbözô kérdôív -a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
27
1
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 35 publications
(31 citation statements)
references
References 16 publications
1
27
1
2
Order By: Relevance
“…However, according to a stricter cut-off score of 6 suggested by Soldatos, Dikeos & Paparrigopoulos 54 , up to 23% of the participants would have complaints comparable to those of insomniac patients. The mean of the GSQS score was lower than the mean score reported for a Hungarian sample of young adults (M = 4.70, SD = 1.78) in Simor et al 35 . The mean of the Sleep diary score in Study 2 was comparable to the mean PSQI score of 1.3 for the same components for the control participants and lower than the score of 6.36 for the participants with sleep disorders in Buysse et al 14 .…”
Section: Resultscontrasting
confidence: 75%
See 1 more Smart Citation
“…However, according to a stricter cut-off score of 6 suggested by Soldatos, Dikeos & Paparrigopoulos 54 , up to 23% of the participants would have complaints comparable to those of insomniac patients. The mean of the GSQS score was lower than the mean score reported for a Hungarian sample of young adults (M = 4.70, SD = 1.78) in Simor et al 35 . The mean of the Sleep diary score in Study 2 was comparable to the mean PSQI score of 1.3 for the same components for the control participants and lower than the score of 6.36 for the participants with sleep disorders in Buysse et al 14 .…”
Section: Resultscontrasting
confidence: 75%
“…To capture the general sleep quality of the last month, we administered the Pittsburgh Sleep Quality Index (PSQI) 14,32 and the Athens Insomnia Scale (AIS) 15,33 . Additionally, in Study 2, we administered a Sleep diary 34 to assess the sleep quality of the last one-two weeks, and the Groningen Sleep Quality Scale (GSQS) 35,36 to capture the sleep quality of the night prior testing.…”
mentioning
confidence: 99%
“…The 14‐item questionnaire assesses last nights’ sleep quality with true/false items (e.g., I feel like I slept poorly last night and I got up in the middle of the night;), and higher total scores indicate poorer subjective sleep quality. In previous studies, the GSQS‐H proved to be a suitable instrument to quantify subjective sleep quality in both healthy individuals and patients with sleep complaints , and in the present study, it showed good internal consistency (Cronbach's alpha = 0.84). In addition to the GSQS‐H, participants were asked to respond to single items regarding their bedtimes, sleep latency (in minutes), and wake up times.…”
Section: Methodssupporting
confidence: 66%
“…Sleep schedules were monitored by sleep agendas, as well as by the adapted version of the Groningen Sleep Quality Scale (Simor et al, 2009) in order to assess individuals' sleep quality the night before the experiment. The data of participants reporting poor sleep quality the night before the experiment (> 7 points) were not considered in the analyses.…”
Section: Participantsmentioning
confidence: 99%